2013
DOI: 10.1017/s0007114513003097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salmon consumption during pregnancy on maternal and infant faecal microbiota, secretory IgA and calprotectin

Abstract: The gut microbiota plays an important role in the development of the immune and gastrointestinal systems of infants. In the present study, we investigated whether increased salmon consumption during pregnancy, maternal weight gain during pregnancy or mode of infant feeding alter the markers of gut immune defence and inflammation. Women (n 123) who rarely ate oily fish were randomly assigned to continue consuming their habitual diet or to consume two 150 g portions of farmed salmon per week from 20 weeks of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 51 publications
0
52
0
2
Order By: Relevance
“…) Both lean and oily fish decreased plasma TAG Miles et al, 2011;Urwin et al, 2012Urwin et al, , 2014Noakes et al, 2012 Investigation of the impact of salmon in pregnancy; diet ingredients for the farmed salmon were specifically selected to be low in contaminants ( The salmon diet increased EPA and DHA in plasma PC in maternal blood, umbilical cord blood and breast milk, and decreased secretory IgA in breast milk (immunological factor provided in the milk). Maternal salmon consumption did not affect maternal or infant fecal microbiota or infant fecal IgA.…”
Section: Moore Et Al 2006mentioning
confidence: 99%
“…) Both lean and oily fish decreased plasma TAG Miles et al, 2011;Urwin et al, 2012Urwin et al, , 2014Noakes et al, 2012 Investigation of the impact of salmon in pregnancy; diet ingredients for the farmed salmon were specifically selected to be low in contaminants ( The salmon diet increased EPA and DHA in plasma PC in maternal blood, umbilical cord blood and breast milk, and decreased secretory IgA in breast milk (immunological factor provided in the milk). Maternal salmon consumption did not affect maternal or infant fecal microbiota or infant fecal IgA.…”
Section: Moore Et Al 2006mentioning
confidence: 99%
“…Prior studies have also observed associations between GWG and maternal microbiota, noting differences in several genera such as Clostridium , Escherichia, Bifidobacterium , and Bacteroides 25,26 . For example, Santacruz et al.…”
Section: Discussionmentioning
confidence: 91%
“…These variables were chosen based on a priori knowledge of differences in microbiota composition. 8,25 Given the relatively small number of infants, we included ≤2 covariates per model. We then determined if the relationship between GWG and fecal microbiota profiles was modified by infant feeding status; that is, did infant microbiota profiles vary by GWG within the group of breast-fed infants (n=66) and within the group of formula-fed infants (n=18).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, subjects with high monounsaturated fat intake did not experience shifts in the relative abundance of any bacterial genera, but did have overall reduced total bacterial load and plasma total- and LDL-cholesterol [49]. In line with these findings, consumption of salmon–which is high in mono and polyunsaturated fats—was not noted to alter fecal microbiota composition in 123 subjects either [50]. Studies in rats have shown that intake of a high-fat diet results in considerably less Lactobacillus intestinalis and disproportionately more propionate and acetate producing species, including Clostridiales, Bacteroides, and Enterobacteriales.…”
Section: Diet and Microbiotamentioning
confidence: 89%